Ki67 expression as a predictor of chemotherapy outcome in low-grade serous ovarian cancer. Issue 4 (28th January 2020) - Grabowski, Jacek P; Martinez Vila, Clara; Richter, Rolf; Taube, Eliane; Plett, Helmut; Braicu, Elena; Sehouli, Jalid
Abstract : Objective: Low-grade serous ovarian cancers characterize a unique clinical pattern and lower chemotherapy responsiveness. The expression level of Ki67 is associated with differences in prognosis; however, this has not yet been evaluated in regard to predicting the outcome of therapy. Methods: Patients with low-grade serous ovarian cancers were identified in an institutional database. Receiver-operator characteristics (ROC) curve analysis was performed to find cut-off values of Ki67 to discriminate patients with residual tumor mass after surgery from maximal debulked patients: therapy response and therapy-free interval (TFI). Results: A total of 68 patients with low-grade serous ovarian cancer were identified. All patients underwent surgery. 61 (89.7%) patients received platinum-based first-line chemotherapy; of these 61 patients, 13 (21.3%) had residual mass (>0 mm) after primary cytoreduction and 11 (18%) received neo-adjuvant chemotherapy. Ki67 ≥3.6% was associated with higher risk of residual mass after surgery (OR 8.1, 95% CI 1.45 to 45.18; p=0.017). Patients with Ki67 <3.6% showed a therapy-free interval of ≥6 months more often (OR 13.9, 95% CI 1.62 to 118.40; p=0.016). In the multivariate analysis of TFI <6 months, including CA125, age at diagnosis, peritoneal carcinomatosis, and ascites, Ki67 <3.6% remained a significant prognostic factor (OR 18.8, 95% CI 1.77 to 199.09; p=0.015). Chemotherapy responsiveness was evaluated in 21 patients who had residual disease and/or received neo-adjuvant chemotherapy. Ki67 ≥4.0% (OR 44.1, 95%CI 2.36-825.17, p = 0.011) was related to a significantly higher response rate (complete and partial response). Conclusions: This is the first study to show an association between Ki67 expression and chemotherapy response, duration of TFI to platinum-based chemotherapy as well as outcome of surgery in low-grade serous ovarian cancers. Further prospective trials should use Ki-67 as a stratification factor to explore the effect of chemotherapy and endocrine strategies.